PRIMARY HYPERPARATHYROIDISM PRESENTING AS ACUTE PANCREATITIS: AN INSTITUTIONAL EXPERIENCE - Sahoo, Jayaprakash; Rashmi, K.G.; Kamalanathan, Sadishkumar; Naik, Dukhabandhu; Mohan, Pazhanivel; Poflakkat, Biju (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES To determine the clinical, biochemical and radiological profile of patients with primary hyperparathyroidism (PHPT) presenting as acute pancreatitis (AP). METHODOLOGY This is a retrospective observational study that has been approved by the institute’s ethical committee. This study included 51 patients diagnosed with PHPT admitted at a tertiary care hospital in Puducherry, India between January 2010 and October 2021, who initially presented as AP. The diagnosis of AP was confirmed if two of the three following features were present: abdominal pain, levels of serum amylase or lipase greater than three times the normal and characteristic features on abdominal imaging. RESULTS Of the 51 patients with PHPT, twelve (23.52%) had pancreatitis- five (9.80%) were acute while seven (13.72%) were chronic. Compared to those without pancreatitis (PHPT-NP), most of those with AP were male, younger (35.20 + 16.11 vs 49.23 + 14.80 years, P=0.05) and had lower intact parathyroid hormone levels (125 vs 519.80, P=0.01). The mean serum calcium levels were similar in both PHPT- AP and PHPT-NP groups (11.66 mg/dL vs 12.46mg/dL, P=0.32). Patients with PHPT-AP presented more frequently with gastrointestinal symptoms like abdominal pain, nausea and vomiting than skeletal and renal manifestations. CONCLUSION This study has shown that AP may be the only presenting feature of PHPT. Acute pancreatitis on the background of elevated serum calcium levels should alert physicians to investigate on endocrine causes of hypercalcemia such as PHPT.